2020
DOI: 10.1002/chem.201904794
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of the Halogen–Zinc Exchange Reaction

Abstract: For the preparation of zinc organometallics bearing highly sensitive functional groups such as ketones, aldehydes or nitro groups, especially mild halogen–zinc exchange reagents have proven to be of great potential. In this Minireview, the latest research in the area of the halogen–zinc exchange reaction is reported, with a special focus lying on novel dialkylzinc reagents complexed with lithium alkoxides. Additionally, the preparation and application of organofluorine zinc reagents and transition‐metal‐cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…They are often compared to the magnesium-based Grignard reagents as they share similar reactivity trends. In particular, organozinc reagents promote CÀ C bond formation under mild conditions, such as in cyclopropanation, [3] nucleophilic addition, [4] carbozincation, [5] halogen-zinc exchange [6] or Negishi crosscouplings. [7] In 1859, Frankland observed that dimethylzinc is more easily obtained from zinc diiodide when coordinating solvents are used.…”
Section: Introductionmentioning
confidence: 99%
“…They are often compared to the magnesium-based Grignard reagents as they share similar reactivity trends. In particular, organozinc reagents promote CÀ C bond formation under mild conditions, such as in cyclopropanation, [3] nucleophilic addition, [4] carbozincation, [5] halogen-zinc exchange [6] or Negishi crosscouplings. [7] In 1859, Frankland observed that dimethylzinc is more easily obtained from zinc diiodide when coordinating solvents are used.…”
Section: Introductionmentioning
confidence: 99%
“…However, the preparation of these organozinc compounds was achieved by a transmetallation reaction of preformed organolithium or magnesium counterparts with zinc halide. Later, various methods were elaborated for preparation of zinc organometallics bearing highly sensitive functional groups [45,46]. However, most of these methods are based on the use of bimetallic zinc-lithium or zinc-magnesium reagents and, despite their indisputable synthetic utility, the use of such activated zinc reagents requires specific conditions together with careful handling.…”
Section: Resultsmentioning
confidence: 99%
“…Unsurprisingly, these bimetallic reagents have already made an impact in organic synthesis, finding widespread applications in core transformations such as deprotonative metallation, metal halogen exchange or C–C bond forming processes. 8 Some key advances in this area include kinetically activated turbo Grignard reagents, i PrMgCl·LiCl, which were first reported in 2004 by Knochel 9 and subsequently evolving to a wide new class of reagents in organic synthesis, being commercially available and generally offering enhanced reactivities and selectivities that are out of reach of conventional Grignard reagents. 10 Through the isolation and characterisation of informative organometallic intermediates from deprotonative metallation reactions of arenes using heterobimetallic bases, Mulvey has introduced the concept of alkali-metal-mediated metallation (AMMM).…”
Section: Introductionmentioning
confidence: 99%